Effect of Probiotics on Sperm Quality in the Adult Mouse - Ana Sanchez-Rodriguez; Ingrid I. D. Idrovo; Rocío Villafranca; Nerea Latorre; Juan Antonio Rielo; Ane Laburu; Sandra Nieto-Román; Daniel Heredia; Rubén González; Virginia García-Cañas; Diego Laxalde; Carolina Simó; et al. (Probiotics and Antimicrobial Proteins, 2025)
The administration of probiotics for the treatment of different diseases has gained interest in recent years. However, few studies have evaluated their effects on reproductive traits. The objective of this study was to examine the effect of two mixtures of probiotics, a commercial probiotic (Vivomixx®) and a mix of Lacticaseibacillus rhamnosus GG and Faecalibacterium duncaniae A2-165, on sperm quality in a mouse model. Adult male mice (8 months old) were used for two experimental and one control groups ( n = 5 each). The probiotics or physiological serum (control) was administered orally, twice a week, during 5 weeks. Sperm were collected from the cauda epididymis, and their total number, motility, kinematics, morphology, and acrosome integrity were assessed in recently collected samples and after a 60-min in vitro incubation. Results showed a higher percentage of normal sperm in both experimental groups, with fewer head abnormalities than in the control. Differences were found among groups in the morphometry of sperm heads, being more elongated in mice treated with probiotics. Sperm from probiotic-treated mice showed similar total motility when compared to the controls, although the proportion of progressively moving sperm and their vigor of motility were lower. Sperm swimming descriptors were measured with a CASA system. Velocity parameters were similar among groups whereas linearity was higher in mice treated with the commercial probiotic. These results suggest that the administration of probiotics may increase the proportion of sperm with normal morphology and lead to modifications in sperm head shape that may enhance sperm swimming. Studies using a longer administration period would be useful in further characterizing the effect of these probiotic mixtures on sperm quality and fertilization capacity.